Hospital Emergency Response of Iran\'s Hospitals against Disasters: A Case Study in Karaj (Tehran University of Medical Sciences, 2016)
Background: Emergency response of hospitals to deal with disasters is essential to success in providing qualified emergency services. The aim of current study was to evaluate emergency response of hospitals in Karaj against disasters. Materials and Methods: This study was a cross sectional one which performed among 13 Karaj hospitals in 2013. To collect data, emergency response Checklist WHO (2011) was utilized with 90 questions prepared in 9 domains (Command and control, Communication,  Safety and security, Triage, Surge capacity, Continuity of essential services, Human resources, Logistics and supply management and Post-disaster recovery).  Data analysis carried out using SPSS version 20 with descriptive tests. Results: mean score of emergency response was 44.17%. The most and the worst dimensions were hospital triage 70.30% and accident reconstruction after the emergency 24.84% respectively. Conclusions: Based on WHO checklist, only 44.17% of studied hospitals were able to respond disaster events. Planning and providing a systematic framework to deal with disasters is a necessity, and the major role of hospitals should not be ignored in providing services considering its priority in plans and budgets in disasters conditions.